Anti‐ageing effects of red ginseng on female Drosophila melanogaster. Issue 6 (5th February 2020) - Hou, Wei; Pei, Jin; Wang, YingPing; Zhang, Jiao; Zheng, HouSheng; Cui, Ranji
Abstract: Red ginseng (RG) was recently reported to extend the lifespan of Drosophila melanogaster . However, the mechanism underlying this effect has not yet been elucidated. The present study aimed to elucidate the molecular mechanisms of the RG‐mediated prolongation of the lifespan of female D melanogaster . In this study, protein changes in 36‐day‐old female D melanogaster were identified using isobaric tag for relative and absolute quantitation (iTRAQ), and levels of differentially expressed proteins were verified by quantitative real‐time PCR and Western blotting. Our studies have shown that RG concentrations of 12.5, 15 and 17.5 mg/mL significantly prolonged the lifespan. Eleven proteins were up‐regulated and 46 were down‐regulated between the RG and control groups; and Pebp1 expression was significantly down‐regulated. In addition, AKT and p‐AKT were down‐regulated, and ERK, p‐ERK and Raf1 were up‐regulated by RG. Therefore, RG significantly prolonged the lifespan of female D melanogaster by reducing the expression of Pebp1, up‐regulating ERK and inhibiting the AKT pathway. RG may be a potential drug for anti‐ageing treatment.